Corrosion Resistance of Cr(III) Conversion Treatments Applied on Electrogalvanised Steel and Subjected to Chloride Containing Media - Tomachuk, C. R. (2010)
The corrosion resistance of pure zinc coatings can be improved through the application of suitable chemical passivation treatments. Hexavalent chromium compounds have widely been used to formulate conversion layers providing better anticorrosive protection as well as anchorage properties to painting systems. However, taking into account that they are produced using hazardous chemical compounds, the development of alternative and “green” technologies with equivalent protective performance is a paramount purpose of many R&D laboratories working around the world. In the present paper, the corrosion behavior of zinc coatings obtained from free-cyanide alkaline baths and later subjected to a Cr3+ based passivation treatment, with and without a sealing treatment, was studied. The experimental work involved electrochemical impedance spectroscopy measurements in 0.5M NaCl solution, surface microstructural and morphological characterization by electronic microscopy as well as chemical analysis by EDXS. The salt spray test was also performed. The analysis and interpretation of all the data coming from this battery of tests allowed inferring that both the Cr3+ based conversion treatment + adequate sealer presented a good corrosion resistance and, therefore, they could be used as neither a polluting nor toxic alternative to the traditional chromate coatings.